Contextual Semantic Analysis of the Word جبهة /Jabhatun/ in Al-Jazeera Media Political News Texts: A Corpus Linguistic Study - Alifaricha, Zazylah (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
This study aims to analyze the contextual meaning of the word جبهة /jabhatun/ in Arabic news texts on Al-Jazeera. This  word frequently appears in reports on politics and international conflicts, but its meaning can vary depending on the context of the sentence and the underlying situation. This study employs a qualitative descriptive method, focusing on sentences or paragraphs in news reports containing the words جبهة and الجبهة. The results indicate that 110 instances of the word were identified, and all instances refer to political contextual meanings rather than physical lexical meanings. The word جبهة no longer carries its literal meaning of “forefront” or “forehead,” but is used metaphorically to refer to a “front,” “battlefront,” or “group united in a conflict.” This meaning is influenced by the sentence context, the news topic, and the political and military situation being discussed. Thus, it can be concluded that understanding contextual meaning is crucial in interpreting vocabulary in Arabic news texts, as a single word can have different variations of meaning depending on the context of its use.